2005
DOI: 10.1111/j.1745-4549.2005.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Storage, Shelf Life and Color of Mango Powder

Abstract: Vacuum-dried mango powder was produced from mango pulp through the addition of glycerol monostearate and tricalcium phosphate at 0.015 kg each per kg mango solids and maltodextrin at 0.62 kg per kg dry mango solids. The mango powder was packed in aluminum foil-laminated pouches and stored in an accelerated storage environment maintained at 90% relative humidity (RH) and 38 ± 2C. The sticky-point moisture content at 38 ± 2C was considered as the maximum moisture content to which the mango powder would remain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
58
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 15 publications
8
58
0
4
Order By: Relevance
“…Non-enzymatic browning in cheddar cheese powder during storage in the range of 20-40°C was found to follow zero-order reaction kinetics with activation energies and Q 10 values being in the range of 15.1-22.3 kcal/ mol and 2.2-3.5, respectively (Kilic et al 1997). Similarly, in another study, it was reported that change in colour of mango powder during storage follows first-order reaction kinetics (Jaya and Das 2005).…”
Section: Introductionmentioning
confidence: 76%
“…Non-enzymatic browning in cheddar cheese powder during storage in the range of 20-40°C was found to follow zero-order reaction kinetics with activation energies and Q 10 values being in the range of 15.1-22.3 kcal/ mol and 2.2-3.5, respectively (Kilic et al 1997). Similarly, in another study, it was reported that change in colour of mango powder during storage follows first-order reaction kinetics (Jaya and Das 2005).…”
Section: Introductionmentioning
confidence: 76%
“…To improve the handling properties of the powders, food grade anti-caking agents (e.g., tricalcium phosphate, silicon dioxide, silicates, phosphates, salts of stearic acid and modified carbohydrates) are also often added together with the drying ingredients (Peleg and Hollenbech 1984;Roos and Karel 1991a;Slade and Levine 1991;Roos 1995;Bhandari et al 1997;Jaya and Das 2005;Jaya et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sticky point temperature can be increased by increasing T g . A sticky-point temperature meter developed by Lazar et al (1956) is used by several authors to measure sticky point temperature (Downton et al 1982;Wallack and King 1988;Buhler and Liedy 1989;Jaya and Das 2005). The test assesses the influence of temperature and moisture content on powder cohesion and is mainly applicable to nearly dry powders.…”
Section: Introductionmentioning
confidence: 99%
“…Another important strategy is addition of carbohydrate polymers to hygroscopic food powders, before or after drying [10][11][12] . The mechanisms by which these carbohydrates may contribute to storage stability of hygroscopic powders are based on different factors that may also be superimposed, which are as follows: (1) competing with host powder components for moisture; (2) acting as a physical barrier between particles, even without completely covering the powder surface; (3) increasing the glass transition temperature (T g ) of the amorphous phase; (4) by forming a moistureprotective barrier on the surface of otherwise hygroscopic particles 1,10 .…”
Section: Introductionmentioning
confidence: 99%